Venous Thromboembolism Risk and Thromboprophylaxis Assessment in Surgical Patients Based on Caprini Risk Assessment Model - Tadesse TA; Kedir HM; Fentie AM; Abiye AA (Dove Medical Press, 2020)
Tamrat Assefa Tadesse, Hanan Muzeyin Kedir, Atalay Mulu Fentie, Alfoalem Araba Abiye Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Tamrat Assefa TadesseDepartment of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, P.O. Box: 9086, Addis Ababa, EthiopiaEmail tamrat.assefa@aau.edu.etPurpose: Venous thromboembolism (VTE) is the most common preventable cause of hospitalization-associated mortality. In the absence of optimal prophylaxis and depending on the type of surgery and patient-related factors, the risk of developing VTE increases by 10% to 50%. We aimed to assess VTE risk and thromboprophylaxis among surgical patients hospitalized at surgical wards of Tikur Anbessa Specialized Hospital (TASH). Addis Ababa, Ethiopia.Materials and Methods: A retrospective cross-sectional study was conducted from September 1, 2018 to February 28, 2019. Data were collected using a pretested observational checklist which is prepared based on the VTE Caprini risk assessment model. Then, the collected data were checked for completeness and finally entered and analyzed using Statistical Package for Social Sciences (SPSS) version 25.Results: Out of 155 admitted patients, almost equal numbers of males (49.68%) and females (50.32%) participated in the study with a mean age of 41.87± 16.84 and an age range of 13 to 89 years. Undergoing major surgery, resting in bed for more than 3 days and having acute infections (including pneumonia) were the most frequently seen VTE risk factors. Most of the study participants (135, 87.10%) were at risk of developing VTE (> 1 Caprini risk score), and 47.11% were in the highest risk category (≥ 5 Caprini score). The maximum and minimum total risk scores were 19 and 1, respectively with a mean score of 4.53± 2.31. Among patients who were at risk of developing VTE and eligible for thromboprophylaxis, only 17.78% received thromboprophylaxis and two ineligible patients received prophylaxis. Parental unfractionated heparin twice or three times per day was the most widely used thromboprophylaxis regimen. A total of 29 (18.71%) patients had one or more contraindication(s) for thromboprophylaxis and three of them took prophylaxis despite the contraindications. Only 3 (1.93%) patients admitted to surgical wards developed VTE during hospitalization.Conclusion: As per the Caprini risk assessment model, the majority of surgical patients treated at TASH were at risk of developing VTE. However, thromboprophylaxis was underutilized. The incidence of VTE was 1.93% in our study.Keywords: VTE risk, Caprini risk score, thromboprophylaxis, surgical patients, Tikur Anbessa Specialized Hospital, Ethiopia